Field-induced single-ion magnet behavior in a cobalt(II) coordination polymer constructed by a mixed bipyridyl-tetracarboxylate strategy. (1st January 2023) - Tang, Wan-Jie; Wu, Si-Tong; Bu, Xiao-Mei; Zhang, Hao-Yu; Wei, Xiao-Qin; Shao, Dong
Graphical abstract: A two-dimensional cobalt(II) coordination polymer constructed by a mixed bipyridyl-tetracarboxylate strategy was reported to show field-induced single-ion magnet behavior. Abstract: A porous two-dimensional (2D) cobalt(II) metal–organic framework (MOF), {[Co(H2 tbca)(bpb)(H2 O)2 ]·bpb}n (H4 tbca  = 1, 2, 4, 5-Benzenetetracarboxylic acid; bpb  = 1, 4-bis(pyrid-4-yl)benzene), was synthesized and structurally characterized. Single crystal X-ray diffraction analysis indicates that the monometallic Co 2+ ion acted as coordination nodes in a distorted octahedral geometry and bridged by H2 tbca 2− and bpb ligands, giving rise to a porous 2D sql network. Thermal analysis reveals high thermal stability of the framework material even losing its guest molecules. Magnetic studies showed that the six-coordinated Co 2+ ions exhibit large easy-plane magnetic anisotropy with the zero-field splitting parameter D  = 62.1 cm −1 . For the presence of significant single-ion magnetic anisotropy, single-ion magnet (SIM) behavior through combined Direct and Raman mechanisms was evidenced with the effective energy U eff  = 31.8 cm −1 . The forgoing result provides a new 2D cobalt(II) SIM-MOF and a potential bipyridyl-tetracarboxylate approach for the construction of SIM frameworks.